Study on the interlayer bonding state of an asphalt pavement based on the stacking peak ratio method - Zhang, Wenwu; Niu, Lei; Wang, Shanshan; Han, Wenyang; Ding, Longting (Frontiers in Energy Research, 2023)
The interlayer bonding of an asphalt pavement significantly influences the mechanical properties and long-term durability of the pavement structure. In order to develop a rapid and comprehensive evaluation method for assessing the interlayer condition of asphalt pavements using 3D GPR, we propose the stacking peak ratio (SPR) method. This method involves stacking the ratio between the amplitude peak of the interlayer and that of surface reflection to evaluate the interlayer state. Comparative analysis with direct shear tests and field measurements leads us to draw several conclusions: the optimal test parameters for the SPR method are a stacking peak ratio at 35 ns with a residence time of 1 us; the SPR method is compatible with various bonding materials and pollution layers, demonstrating its ability to effectively assess the bonding state of asphalt pavements; field tests further validate that the SPR approach can identify insufficient layer bonding and predict potential flaws in advance. Through our test findings and data analysis, it is evident that this SPR approach provides theoretical support and technological assistance for promptly evaluating the bonding status in asphalt pavements.